Землетрясения в Днепровско-Донецком авлакогене - Кутас, В.В.; Андрущенко, Ю.А.; Омельченко, В.Д.; Лящук, А.И.; Калитова, И.А. (Геофизический журнал, 2015)
Наведено результати аналізу хвильової картини і спектрограм сейсмічних подій у Дніпровсько-Донецькому авлакогені, зареєстрованих групою станцій Головного центру спеціального контролю ДКАУ. Вогнища землетрусів з магнітудою mb = 3,0; 4,5 знаходяться на глибині 3-10 км на межі зон грабену - центральної і південної прибортової - поблизу м. Полтава і на північному крайовому розломі поблизу м. Лебедин Сумської обл. Розглянуто зв'язок локальної сейсмічності з особливостями будови земної кори в цих районах авлакогену, встановленими за геолого-геофізичними даними. Results of analysis of the wave pattern and spectrograms of seismic events in the Dnieper- Donets aulakogen registered by a group of stations of the Main center for special control of ГКАУ have been presented. The sources of the earthquakes with magnitude mb = 3,0; 4,5 are situated at a depth of 3-10 km at the boundary of graben zones: the central zone and the southern one adjacent to the edge near Poltava city and also on the northern fault near Lebedyn city of Sumy district. Relationship of local seismicity and special features of the earth crust structure in these areas of aulakogen revealed according to geological-geophysical data has been considered.